2020
DOI: 10.3390/nano10081561
|View full text |Cite
|
Sign up to set email alerts
|

Green Preparation of Fluorescent Nitrogen-Doped Carbon Quantum Dots for Sensitive Detection of Oxytetracycline in Environmental Samples

Abstract: Nitrogen-doped carbon quantum dots (N-CQDs) with strong fluorescence were prepared by a one-step hydrothermal method using natural biomass waste. Two efficient fluorescent probes were constructed for selective and sensitive detection of oxytetracycline (OTC). The synthesized N-CQDs were characterized by UV-visible absorption spectra, fluorescence spectra, Fourier transform infrared spectroscopy (FT-IR), X-ray photon spectroscopy (XPS), atomic force microscopy (AFM), and high-resolution transmission electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 74 publications
3
20
0
Order By: Relevance
“…The HRTEM image indicated that RSFC-CDs had a graphite-like crystalline framework with a lattice spacing of 0.278 nm ( Figure 2B ), which was consistent with the (100) planes of graphitic carbon. 27 , 28 The recognizable diffraction peak (2θ=23.7°) in the XRD pattern ( Figure 2D ) revealed an amorphous carbon phase of RSFC-CDs, which corresponded with the HRTEM image. 29
Figure 2 ( A ) Transmission electron microscope (TEM) image of Radix Sophorae Flavescentis carbonisata-based carbon dots (RSFC-CDs).
…”
Section: Resultssupporting
confidence: 58%
“…The HRTEM image indicated that RSFC-CDs had a graphite-like crystalline framework with a lattice spacing of 0.278 nm ( Figure 2B ), which was consistent with the (100) planes of graphitic carbon. 27 , 28 The recognizable diffraction peak (2θ=23.7°) in the XRD pattern ( Figure 2D ) revealed an amorphous carbon phase of RSFC-CDs, which corresponded with the HRTEM image. 29
Figure 2 ( A ) Transmission electron microscope (TEM) image of Radix Sophorae Flavescentis carbonisata-based carbon dots (RSFC-CDs).
…”
Section: Resultssupporting
confidence: 58%
“…Moreover, several studies have used biomass waste for obtaining CQDs, including citrus [ 8 , 9 ], kitchen waste [ 10 ], mango peel [ 11 ], banana peel [ 12 ], expired milk [ 13 ], egg shell [ 14 ], and agarose waste [ 15 ], all exhibiting good chemical and optical properties, and obtained carbon dots were applicable for the bioimaging, biosensing, and environmental monitoring. A significant challenge in the fabrication of biomass-derived CQDs represents obtaining CQDs with a high quantum yield.…”
Section: Introductionmentioning
confidence: 99%
“…XPS is used to characterize the electronic state of the elements present on the surface of CDs, their elemental composition, as well as their other surface attributes. In XPS, a beam of X-rays is directed at the CDs specimen, followed by the irradiation of the sample and concurrent measurement of kinetic energy and number of electrons [155,[200][201][202]. Figure 11 demonstrates the ideal XPS spectra for CDs characterization [167].…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 99%